Factors Influencing UTHM Catering Students to Venture into Business as Side Income - Nur Yusrina Aida Razali; Tukiran, Nor Anis Intan Aqiah; Ahmad, Noraziah (Research and Innovation in Technical and Vocational Education and Training, 2024)
This study was conducted to identify the factors influencing UTHM catering students to venture into business as a side income. Aspects studied include internal factors, external factors, and the dominant factors that influence UTHM catering students in venturing into business. 198 UTHM catering students from Cohort 13 to Cohort 18 were selected, with 132 samples being part of this study. Data were gathered using random sampling and analyzed using the Statistical Package for the Social Sciences (SPSS) version 25. The study found that the internal factor of interest (mean = 3.40) and external factors of finance and skills (both mean = 3.42) are the dominant factors influencing students to engage in business as a side income. The rising number of student entrepreneurs has sparked interest in the driving forces behind this trend. The findings demonstrate that motivation, social networks, financial support, and an entrepreneurial mindset all have a major impact on UTHM catering students’ decisions to start a business as a side source of income. The study’s conclusions also provide valuable insight into students’ entrepreneurial goals and behaviors, highlighting the importance of cultivating an entrepreneurial mindset, providing financial resources, and building a network of people who can assist one another.